On maximal stable orders on an inverse semigroup of finite rank with zero - Derech, V. D. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We consider maximal stable orders on semigroups that belong to a certain class of inverse semigroups of finite rank.